The Curious Case of Twin Fast Radio Bursts: Evidence for Neutron Star Origin? - Bera, Apurba; James, Clancy; Deller, Adam T; Bannister, K.W.; Shannon, R.M.; Scott, Danica R.; Gourdji, K.; Marnoch, L.; Glowacki, Marcin; Ekers, Ronald D.; Ryder, S.; Dial, T. (2024)
Fast radio bursts (FRBs) are brilliant short-duration flashes of radio emission originating at cosmological distances. The vast diversity in the properties of currently known FRBs and the fleeting nature of these events make it difficult to understand their progenitors and emission mechanism(s). Here we report high time resolution polarization properties of FRB 20210912A, a highly energetic event detected by the Australian Square Kilometre Array Pathfinder (ASKAP) in the Commensal Real-time ASKAP Fast Transients survey, which show intraburst position angle (PA) variation similar to Galactic pulsars and unusual variation of Faraday rotation measure (RM) across its two sub-bursts. The observed intraburst PA variation and apparent RM variation pattern in FRB 20210912A may be explained by a rapidly spinning neutron star origin, with rest-frame spin periods of ∼1.1 ms. This rotation timescale is comparable to the shortest known rotation period of a pulsar and close to the shortest possible rotation period of a neutron star. Curiously, FRB 20210912A exhibits a remarkable resemblance to the previously reported FRB 20181112A, including similar rest-frame emission timescales and polarization profiles. These observations suggest that these two FRBs may have similar origins.